A comparison of seasonal variability of Arabian Gulf and the Sea of Oman pelagic ecosystems. Issue 2 (3rd April 2019) - Piontkovski, Sergey A.; Hamza, Waleed M.; Al-Abri, Nader M.; Al-Busaidi, Saud S.Z.; Al-Hashmi, Khalid A.
Abstract : This overview compares algal blooms and pelagic fisheries of the Arabian Gulf with the Sea of Oman. The data consist of remotely sensed characteristics, directly sampled and modeled. Elucidated seasonal trends were based on 15-year seasonal means, as well as weekly time series of physical parameters. The environmental characteristics (namely photosynthetically available radiation, atmospheric pressure, temperature, wind, aerosol optical thickness, surface currents, surface temperature, salinity, concentration of dissolved oxygen, nitrates, phosphates, chlorophyll- a, net primary production, phytoplankton, zooplankton biomass, fish larvae abundance, small and large pelagic fish catches) were compared between regions. In Sea of Oman, high concentrations of chlorophyll- a were associated with relatively high concentrations of nitrates and phosphates, as well as kinetic energy of surface currents which exceeded that in Arabian Gulf. The dinoflagellate Noctiluca scintillans is one dominat alga in the Sea of Oman, whereas diatom species are more common in the Arabian Gulf blooms. In general, the phytoplankton and zooplankton species diversity during winter was higher than in summer periods. Catches of small pelagic fish (in particular sardines) in the Sea of Oman exceeded that in the Arabian Gulf. This might be associated, in part, with differences in trophic levels interactions. The turnover rate of the net primary production through zooplankton in Sea of Oman was found to be much higher than in Arabian Gulf waters.